THE IMPACT OF NURSING ROLE AND EXPERIENCE ON PATIENT SATISFACTION IN SAUDI ARABIA - Nawal Nafee Tfilan Al Rowaili, Abdulah Nafee Tfillan Al Ruwaili, ,Azizah Maskam Aldhafeeri, Awad Naif Slman Aldferi, Haya Aqeel Aldafeeri, And Miad Khulaif Murdhi Aljamee, , (Chelonian Research Foundation, 2022)
Background: Nursing roles and experience are essential factors that contribute to patient satisfaction and the quality of healthcare services. This study aims to investigate the impact of nursing roles (registered nurse, nursing assistant, and nursing technician) and years of experience on patient satisfaction in Saudi Arabia. Methods: A cross-sectional survey design was used to collect data from a sample of 500 nurses and 1,500 patients in three major hospitals in Riyadh, Saudi Arabia. The nurses provided information on their roles and years of experience, while the patients completed the Patient Satisfaction Questionnaire (PSQ-18). Multiple linear regression analysis was used to examine the relationships between nursing roles, experience, and patient satisfaction, while controlling for relevant demographic and clinical factors. Results: Nursing role and experience were significant predictors of patient satisfaction, after controlling for age, gender, education, and health status. Registered nurses had higher patient satisfaction scores than nursing assistants and technicians (β = 0.15, p < 0.01). Nurses with more years of experience also had higher patient satisfaction scores (β = 0.22, p < 0.001). The interaction between nursing role and experience was not significant. Discussion: The study highlights the importance of the nursing workforce in enhancing patient satisfaction and healthcare quality in Saudi Arabia. The findings suggest that investing in the education, training, and retention of registered nurses and experienced nurses can contribute to better patient outcomes and experiences. The implications for nursing practice, education, and policy, as well as the limitations and future directions for research, are discussed. Keywords: nursing roles, experience, patient satisfaction, healthcare quality, Saudi Arabia